2017
DOI: 10.1002/adfm.201704470
|View full text |Cite
|
Sign up to set email alerts
|

Highly Condensed Boron Cage Cluster Anions in 2D Carrier and Its Enhanced Antitumor Efficiency for Boron Neutron Capture Therapy

Abstract: An attempt is made to apply layered double hydroxide (LDH) as a boron delivery carrier for boron neutron capture therapy (BNCT), which needs a sufficient amount of boron in tumor cells for its successful administration. To meet this requirement, a nanohybrid (BSH-LDH), mercaptoundecahydrocloso-dodecaborate (BSH) anionic molecules in LDH, is developed as a boron delivery system. The cellular boron content upon permeation of BSH-LDH nanoparticles (42.4 µg 10 B 10 −6 cells) in U87 glioblastoma cell line is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…The transmission electron microscopy (cryo-TEM and TEM) images of BCVs revealed clearly that BCVs was dispersed as individual particles with a well-defined spherical bilayer/core-shell structure. This similar case was reported that Nie's group 15) prepared DOX and paclitaxel (TAX) coloaded mPEG-PLGA nanoparticles (NPs-DOX-TAX) with size of approximate 250 nm by DLS. The morphology of NPs-DOX-TAX was examined by TEM.…”
Section: Resultssupporting
confidence: 78%
“…The transmission electron microscopy (cryo-TEM and TEM) images of BCVs revealed clearly that BCVs was dispersed as individual particles with a well-defined spherical bilayer/core-shell structure. This similar case was reported that Nie's group 15) prepared DOX and paclitaxel (TAX) coloaded mPEG-PLGA nanoparticles (NPs-DOX-TAX) with size of approximate 250 nm by DLS. The morphology of NPs-DOX-TAX was examined by TEM.…”
Section: Resultssupporting
confidence: 78%
“…In biomedical applications, one of the most significant factors in utilizing layered nanomaterials is biocompatibility. Among various 2D layered crystal structures, LDHs have been established as highly biocompatible, and their related nanohybrids are readily applicable for therapeutic and diagnostic uses such as anti-cancer, anti-inflammatory, antibiotic, antioxidant efficacy, and bio-imaging [33][34][35][36][37][38][39][40][41][42][43][44]. As has been well documented, efficient drug delivery carriers should not only be biocompatible to ensure safety aspects of nano delivery vehicles, but also be suitable to stabilize and protect biomolecules against harsh physical and biochemical attacks in biological environments, subsequently to deliver genes/drugs into the target-specific tissue and release them in the controlled manner.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies on LDH-based nanohybrids for multimodal imaging as well as desirable combination therapies, which use more than one medication or modality to realize synergistic treatment. LDHs have been extensively studied as a theranostic delivery carrier for a variety of therapies, including chemo-, gene-, photo-, boron neutron capture-, and even immunotherapy [64,65,66,67,68,69,70,71,72,73,74,75,76,77,78].…”
Section: Ldh Nanohybrids For Bio-imaging Applications With Therapementioning
confidence: 99%